2012
DOI: 10.5045/kjh.2012.47.4.286
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepcidin levels and iron parameters in children with iron deficiency

Abstract: BackgroundIron deficiency (ID) and iron deficiency anemia (IDA) are common nutritional disorders in children. Hepcidin, a peptide hormone produced in the liver, is a central regulator of systemic iron metabolism. We evaluated whether serum hepcidin levels can diagnose ID in children.MethodsSera from 59 children (23 males and 36 females; 5 months to 17 years) were analyzed for hepcidin-25 by ELISA. Patients were classified according to hemoglobin level and iron parameters as: IDA, (N=17), ID (N=18), and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
53
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 30 publications
12
53
1
Order By: Relevance
“…They increase the pro- trols (220.44±49.52ng/mL). This result is not compatible with the literature [1]. This finding can be attributed to the small number of patients with iron-deficiency anemia.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…They increase the pro- trols (220.44±49.52ng/mL). This result is not compatible with the literature [1]. This finding can be attributed to the small number of patients with iron-deficiency anemia.…”
Section: Discussioncontrasting
confidence: 56%
“…Although commercial tests are available, the absolute values of hepcidin have not been established. It has been reported that reference values changed according to age, gender and the method used [1,6,11]. Although there are large-scale population studies in adults; there are no studies on children on this scale [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon has also been observed in children with iron deficiency (Choi et al 2012), the most common form of iron deficiency anemia, which is characterized by a reduction of hepcidin. In contrast, Hb concentrations in LC patients correlated negatively with hepcidin levels, which is a type of anemia characterized by induction of hepcidin.…”
Section: Anemia and Hepcidin In Hf Patientsmentioning
confidence: 87%